Nonconventional Initiation Complex Assembly by STAT and NF-κB Transcription Factors Regulates Nitric Oxide Synthase Expression - Farlik, Matthias (Cell Press, 2010)
Transcriptional regulation of the Nos2 gene encoding inducible nitric oxide synthase (iNOS) requires type I interferon (IFN-I) signaling and additional signals emanating from pattern recognition receptors. Here we showed sequential and cooperative contributions of the transcription factors ISGF3 (a complex containing STAT1, STAT2, and IRF9 subunits) and NF-κB to the transcriptional induction of the Nos2 gene in macrophages infected with the intracellular bacterial pathogen Listeria monocytogenes. NF-κB preceded ISGF3 at the Nos2 promoter and generated a transcriptional memory effect by depositing basal transcription factor TFIIH with the associated CDK7 kinase for serine 5 phosphorylation of the RNA polymerase II (pol II) carboxyterminal domain (CTD). Subsequent to TFIIH deposition by NF-κB, ISGF3 attracted the pol II enzyme and phosphorylation at CTD S5 occurred. Thus, STATs and NF-κB cooperate through pol II promoter recruitment and the phosphorylation of its CTD, respectively, as a prerequisite for productive elongation of iNOS mRNA.